Algae of Itahari Municipality and its adjoining area, Eastern Nepal - Shrestha, Sabitri; Rai, Shiva Kumar; Dhakal, Min Raj (International Journal of Applied Sciences and Biotechnology, 2013)
A total fifty-two algal taxa belonging to 3 classes and 21 families were reported from Itahari and its adjoining areas. Among them, Chlorophycean taxa were rich with 36 taxa followed by 9 taxa of Cyanophyceae and 7 taxa of Bacillariophyceae. Sixteen taxa were identified up to generic level only and rest 36 up to species level. Most of the species were collected from aquatic habitat both lotic and lentic, some were from soil and few as epiphytic. Out of 36, ten algae viz., Oscillatoria tenuis, Lyngbya martensiana, Achnanthes brevips, Pithophora varia, Stigeoclonium fasciculare, Oedogonium gallicum, Spirogyra crassa, S. gracilis, Closterium acerosum var. tumidum and Cosmarium nitidulum were new to Nepal. Dominant genera were Spirogyra, Oscillatoria, Closterium, Cosmarium, Navicula and Hydrodictyon collected from ponds, moist soils, ditches, and canals. DOI: http://dx.doi.org/10.3126/ijasbt.v1i1.7920 Int J Appl Sci Biotechnol, 2013, Vol. 1(1): 5-10